The attitudes of parents and children towards restoration of deciduous molar teeth with stainless steel crown (SSC) in the Dental Hospital University of Baiturrahmah - Sri P. Utami; Hanifa U. Dwi; Hamdy Lisfriza (Journal of Dentomaxillofacial Science, 2020)
Objective: This study aims to examine the attitude of parents and children towards the restoration of primary molars with stainless steel crowns (Stainless Steel Crown / SSC) at the Dental and Mouth Hospital of Baiturrahmah University. Materials and Methods: this was a cross sectional descriptive study consisting of 40 children aged 6-9 years and who had been treated with the SSC for the past 3-6 months. Subjects and Methods: consists of parents and children who fill out a questionnaire containing 11 questions consisting of 6 questions for children and 5 questions for parents. Statistical analysis: Data analysis using t-test at a significant level of P> 0.05.Results: In general, children's attitude scores were positive, and the average attitude Obtained score was 10:17 ± 1:05, 97.5% of children Obtained good attitudes. Also Parental attitude scores are positive; Reviews their attitudes on average were Obtained to be 14.95 ± 1.9, 95% of parents rated good attitude.Conclusion:The attitude towards SSC scores of children are good and do not depend on age, gender. Almost all parents are satisfied with the presentation, the agreed by them about the children, they receive the crown well